Dynamics of submaximal effort soccer instep kicking - Nunome, H.; Inoue, K.; Watanabe, K.; Iga, T.; Akima, H. (Journal of Sports Sciences, 2018)
During a soccer match, players are often required to control the ball velocity of a kick. However, little information is available for the fundamental qualities associated with kicking at various effort levels. We aimed to illustrate segmental dynamics of the kicking leg during soccer instep kicking at submaximal efforts. The instep kicking motion of eight experienced university soccer players (height: 172.4 ± 4.6 cm, mass: 63.3 ± 5.2 kg) at 50, 75 and 100% effort levels were recorded by a motion capture system (500 Hz), while resultant ball velocities were monitored using a pair of photocells. Between the three effort levels, kinetic adjustments were clearly identified in both proximal and distal segments with significantly different (large effect sizes) angular impulses due to resultant joint and interaction moments. Also, players tended to hit an off-centre point on the ball using a more medial contact point on the foot and with the foot in a less upright position in lower effort levels. These results suggested that players control their leg swing in a context of a proximal to distal segmental sequential system and add some fine-tuning of the resultant ball velocity by changing the manner of ball impact.